Centimeter grid scale used at Harshnath Temple Complex - Temples of India Project Team (Jio Institute, 2024)
The centimeter grid scale is placed on the pillar capital to record the proportion of the carvings, Harshnath Temple Complex, Sikar district, Rajasthan. (Image courtesy: Mrunal Nidadavolu)